Key technology and application scenarios of NFV - Yafei TANG; Sufen LI (Dianxin kexue)
Network virtualization aims to realize the decoupling of hardware and software by virtualization,and share the resource according to service size by cloudification,thus supporting the telecom business with features of high flexibility,maintainability,usability and immediate return of investment.The virtualization architecture and key technologies of NFV were introduced,and the typical NFV application scenarios for telecom operators were presented to promote the research and implementation of telecom network virtualization technology.